Preparation, Characterization of Novel Cadmium-Based Metal-Organic Framework for Using as a Highly Selective and Sensitive Modified Carbon Paste Electrode in Determination of Cu(II) Ion. Issue 4 (4th July 2021) - Deghadi, Reem G.; Eliwa, Ayman S.; Ali, Aya E.; Hosny, Wafaa M.; Mohamed, Gehad G.
ABSTRACT: A new organic linker Schiff base (H2 L) derived from 4-aminobenzoic acid and 2-carboxybenzaldehyde has been successfully synthesized and characterized. The synthesized linker Schiff base was designed to be used in preparation of a new cadmium-based metal-organic framework (Cd-MOF) by sonochemical synthesis, and characterized by using Fourier-transform infrared spectroscopy (FT-IR), powder X-ray diffraction (PXRD), Brunauer-Emmett-Teller (BET), scanning electron microscope (SEM), energy dispersive X-ray (EDX), and thermal analysis. Under an optimum set of synthesis conditions, uniform cubic crystals with average size 44–69 nm and a Langmuir surface area of 163.461 m 2 /g were produced within 60–75 min by crystal system orthorhombic. The synthesized Cd-MOF was incorporated as an ionophore in a carbon paste electrode for Cu(II) ion determination in different real water samples. The proposed carbon paste electrode showed a Nernstian slope of 30.15 ± 0.35 mV decade −1 covering a linear range of 1.0 × 10 −7 – 1.0 × 10 −1 mol L −1 and the detection limit was 7.5 × 10 −8 mol L −1 with long-time stability of more than two months over pH range of 2.5–6.5 and fast response time of 10 s. The proposed sensor was highly selective for Cu(II) ions. The synthesized Cd-MOF had mesoporous structure and this supported the mechanism of Cu(II) ion successful determination.